2021
DOI: 10.3390/app11073198
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of One-Way Road Tunnel Tube Used for Bi-Directional Traffic under Fire Scenarios

Abstract: We have set up a Computational Fluid Dynamics (CFD) modeling, and performed a user evacuation model, for evaluating the risk level in one-way road tunnel tube when used for bi-directional traffic in particular circumstances. The simulations were carried out by considering both peak-hour traffic volumes during the day and off-peak hours overnight. The investigated one-way tube is ventilated by natural ventilation only, and has a length of less than 1000 m. With reference to the worst environmental conditions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Once the FDS tool was validated, a grid sensitivity analysis was carried out in order to identify an adequate mesh fineness. The results of this analysis, detailed in Caliendo et al [16,17], showed that the cubic cells of 0.4 m side were appropriate for correctly discretizing the investigated tunnel; in particular, 1,095,255 cells were used.…”
Section: Validation and Mesh Finenessmentioning
confidence: 98%
See 1 more Smart Citation
“…Once the FDS tool was validated, a grid sensitivity analysis was carried out in order to identify an adequate mesh fineness. The results of this analysis, detailed in Caliendo et al [16,17], showed that the cubic cells of 0.4 m side were appropriate for correctly discretizing the investigated tunnel; in particular, 1,095,255 cells were used.…”
Section: Validation and Mesh Finenessmentioning
confidence: 98%
“…); it is then followed by a constant HRR max phase. Details regarding the assumptions made for the yields of combustion products are reported in Caliendo et al [16,17].…”
Section: Fire Scenariosmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) modeling is the most suitable tool for reproducing a fire; some of its applications, with reference to road tunnels, can be found in Caliendo et al [25][26][27][28][29][30][31]. In this paper, the Fire Dynamics Simulator (FDS) version 6.7.3 [45], which has been widely reported in the literature regarding the simulation of fires in road tunnels, was used as a CFD code.…”
Section: Fire Simulation Codementioning
confidence: 99%
“…With reference to our previous studies, it is also worth highlighting that we did not investigate user safety in the earlier paper [25], while in other studies, we evaluated only the safety level of tunnel users in the event of a fire (e.g., Caliendo et al [26][27][28][29][30][31][32], Caliendo and De Guglielmo [33][34][35][36], and Caliendo and Genovese [37]), but not resilience. In other words, tunnel resilience and user safety were not coupled to each other; consequently, the effects of a strategy to recover the functionality of a tunnel that might influence user safety or vice versa were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, gas-monitoring systems in underground mines are used successfully to predict the re-entry times after blasting operations [ 31 ]. CFD numerical simulations are also carried out for evaluating the risk level in road tunnels under fire scenarios while considering natural ventilation [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%